Reinas e infantas en la decoración escultórica del claustro basilical de San Isidoro de León - Morais Vallejo, Emilio (Estudios humanísticos. Geografía, historia y arte, 2001)
The main cloister of San Isidoro of León, reconstructed from 1731, features an scuptural decoration of relieves covering the upper part of the North and East walls. The main motives are portraits of queens and infantas of the medieval monarchy of León and Castilla, accompanied by sibyls, biblical women, allegories, triunphal chariots, etc. A decoration which is used to exalt the values of the monarchy, legitimized by tradition.